Outcome of eminectomy combined with discectomy and silastic interpositional graft for temporomandibular joint dysfunction: a retrospective study of 20 years. Issue 7 (September 2020) - Baheerathan, N.N.; Sayan, A.; Demir, E.; Ilankovan, V.
Abstract: Internal derangement of the temporomandibular joint (TMJ) is usually treated conservatively, but about 5% require surgical treatment. We designed a retrospective study to assess the long-term outcomes of eminectomy combined with discectomy and silastic interpositional graft in 44 patients who had chronic TMJ dysfunction that had not responded to traditional conservative treatment and arthrocentesis. The maximum mouth opening, pain score, Wilkes stage, and clinical dysfunction index were measured before, and two years after, operation. All the patients showed significant improvement in mouth opening and reduced pain scores (p < 0.0001 in each case). There were no long-term operative complications, and postoperative magnetic resonance scans showed that the silastic interpositional graft was in a stable position with no evidence of degenerative changes on the surfaces of the joint and no lymphadenopathy.